2015
DOI: 10.1177/1403494815610182
|View full text |Cite
|
Sign up to set email alerts
|

Measles among migrants in the European Union and the European Economic Area

Abstract: Aims: Progress towards meeting the goal of measles elimination in the EU and the European Economic Area (EEA) by 2015 is being obstructed, as some children are either not immunized on time or never immunized. One group thought to be at increased risk of measles is migrants; however, the extent to which this is the case is poorly understood, due to a lack of data. This paper addresses this evidence gap by providing an overview of the burden of measles in migrant populations in the EU/EEA. Methods: Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 32 publications
0
38
0
1
Order By: Relevance
“…In Germany, foreign-born children had a three-fold higher risk of being unvaccinated, thus being more susceptible to measles. The situation is similar in Italy and Spain, with coverage rates higher among native populations than among foreign-born children [38,41]. However, Mikolajczyk reported no difference in vaccination coverage between migrant and non-migrant children [13].…”
Section: Measles Mumps and Rubellamentioning
confidence: 97%
See 3 more Smart Citations
“…In Germany, foreign-born children had a three-fold higher risk of being unvaccinated, thus being more susceptible to measles. The situation is similar in Italy and Spain, with coverage rates higher among native populations than among foreign-born children [38,41]. However, Mikolajczyk reported no difference in vaccination coverage between migrant and non-migrant children [13].…”
Section: Measles Mumps and Rubellamentioning
confidence: 97%
“…A recent systematic review highlighted the lack of harmonized data on measles outbreaks and vaccination coverage among migrants in Europe [38]. Serological studies investigated the susceptibility to measles among migrants and refugees, estimating a prevalence of seronegative individuals between 6 and 13% [40,42,43].…”
Section: Measles Mumps and Rubellamentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that diseases that can be prevented by vaccination cause flare-ups in reception and holding centers [39,42,43,44,45,46,47,48]. Outbreaks are generally more severe in refugee camps [48].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%